Indicators for Water Resource Management - Sannchez, Junn Ra; Galvin, Denise; Bellot, Juan; Bonet, Andreu; Pena, Juan; Aledo, Antonio; Abad, Jose (Annals of Arid Zone, 2016)
Physical, social and institutional indicators can be relied on to reveal an inter-play of change. However, it is sometimes problematic to link the dynamics of this change with the reality of a situation. The Marina Baixa County located in the Alicante province of Spain, has been the focus of intensive work to determine the indicators of change in the hydrological network, as well as water supply and demand patterns for incorporation into present and future policy. An aggregation of the results from four studies undertaken over a decade is presented here. Indicators that have been developed provide a rich bank of knowledge about the co-dynamics of the physical, institutional and social aspects of this water using community that currently suffers a seasonal water deficit. This paper attempts to provide an explanation of the meaningfulness of these indicators, as well as a review of how they are being used in a context of change.